Development and simulations of aircraft guidance system using a 3-degree-of-freedom point mass model - Sudars, Martins (Aviation (Vilnius, Lithuania), 2009)
Numerical simulations play an essential role in the development and testing of navigation and guidance algorithms, especially when developer must keep the development costs as low as possible. Low budget development focuses mainly on utilization of numerical flight mechanics simulators including optimization and hardware in loop tests. Reliable, high fidelity results can be easily obtained by numerical simulations of flight dynamics utilizing computing power provided by a normal off-the-shelf home PC. However, it still requires a simple, but good and valid model of the aircraft and environment. This paper describes an approach to a numerical simulation of aircraft motion that respects the requirement for a full environment high fidelity model and keeps a good interface for further development of attitude control. The goal is achieved by directly specifying the aerodynamic angles of the vehicle in the simulation environment by the guidance system, which can later be used as input for attitude control algorithms. It is proved how an appropriate selection of reference frames and formulation of laws of motion gives very quick and reliable results by employing large integration time steps that would be difficult to achieve in 6-degree-of-freedom simulations. This paper also investigates the range of applicability, advantages, and drawbacks of this method. An example of an aerodynamic angle-based guidance law for a UAV is explained and demonstrated by figures.